Autopsy Findings of 15,823 Natural Deaths in Accra, Ghana - Muazzam, MG; Tette, Y; Gyasi, R (Bangladesh Journal of Medical Science, 2011)
DOI: http://dx.doi.org/10.3329/bjms.v1i1.7847 Bangladesh Journal of Medical Science Vol.1(1) 1994 pp.12-21